Implementation of Digital Marketing for MSMEs in Salatiga City Through Content Marketing Utilizing Artificial Intelligence - Hendraminetta, Amara Jisella; Ageng, Imanuel Rizky; Handal, Ray Isa Cipta; Pratama, Rafael Oka Putra; Putri, Christina Ari Pramono (Institut Teknologi dan Bisnis Asia Malang, 2025)
Purpose: This study aims to assist MSME Yasuka Grill & Shabu-Shabu in Salatiga in implementing digital marketing using content creation and Artificial Intelligence (AI) for product visuals, captions, and website development, addressing challenges in digital adaptation and market reach. Method: A one-month community service was conducted through interviews, observation, hands-on training, and mentoring. Activities included social media optimization (Instagram/TikTok), website creation via Google Sites, and AI tool utilization (ChatGPT, Canva, CapCut). Practical Applications: The program equipped MSMEs with practical digital marketing skills, enabling independent content creation and platform management, enhancing brand visibility and customer engagement. Conclusion: The intervention yielded structured content, an active website, and improved social media performance, increasing competitiveness. It demonstrates the effectiveness of AI-integrated digital marketing in empowering MSMEs, offering a replicable model for similar businesses.